Improving patient flow in pre-operative assessment. Issue 1 (7th January 2015) - Stark, Cameron; Gent, Anne; Kirkland, Linda
Abstract: Annual patient attendances at a pre-operative assessment department increased by 24.8% from 5659 in 2009, to 7062 in 2012. The unit was staffed by administrative staff, nurses, and health care assistants (HCA). Medical review was accessed via on call medical staff, or notes were sent to anaesthetists for further review. With rising demand, patient waits increased. The average lead time for a patient (time from entering the department to leaving) was 79 minutes. 9.3% of patients attended within two weeks of their scheduled surgery date. 10% of patients were asked to return on a later day, as there was not sufficient capacity to undertake their assessment. There were nine routes of referral in to the department. Patients moved between different clinic rooms and the waiting area several times. Work patterns were uneven, as many attendances were from out-patient clinics which meant peak attendance times were linked to clinic times. There were substantial differences in the approaches of different nurses, making the HCA role difficult. Patients reported dissatisfaction with waits. Using a Lean quality improvement process with rapid PDSA cycles, the service changed to one in which patients were placed in a room, and remained there for the duration of their assessment. Standard work was developed for HCWs and nurses. Rooms were standardised using 5S processes, and set up improved to reduce time spent looking for supplies. A co-ordinator role was introduced using existing staff to monitor flow and to organise the required medical assessments and ECGs. Timing of booked appointments were altered to take account of clinic times. Routes in to the department were reduced from nine to one. Ten months after the work began, the average lead time had reduced to 59 minutes. The proportion of people attending within two weeks of their surgery decreased from 9.3% to 5.3%. Referrals for an anaesthetic opinion decreased from 30% to 20%, and in the month reviewed no one had to return to be seen as a result of limited capacity.